PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN LKPD ELEKTRONIK UNTUK MENINGKATKAN HASIL BELAJAR PPKN PADA SISWA SEKOLAH DASAR - Fitriyaningsih, Uchti; Chamdani, Muh.; Salimi, Moh (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to find out how the concept of Islamic leadership of school principals improves teacher communication ethics in education units. The study aimed to improve Civic Education learning outcomes through the implementation of Problem Based Learning (PBL) aided electronic worksheets. This classroom action research was conducted in three cycles. The subjects were teacher and students of third grade at SDN 1 Gesikan. The data were qualitative and quantitative. Data collection techniques were observation, interviews, and tests. Data validity used triangulation of sources and triangulation of techniques. Data analysis included data reduction, data presentation, and drawing conclusions. The result indicated that the improvement of learning outcomes were 75.00% in the first cycle, 82.50% in the second cycle, and 90.00% in the third cycle. It concludes that the implementation of Problem Based Learning (PBL) aided electronic worksheets improves Civic Education learning outcomes about rights and obligations to third grade students of SDN 1 Gesikan in academic year of 2022/2023